A comparative study on in vitro osteogenic priming potential of electron spun scaffold PLLA/HA/Col, PLLA/HA, and PLLA/Col for tissue engineering application. - Hanumantha Rao Balaji Raghavendran; Subramaniam Puvaneswary; Sepehr Talebian; Malliga R Murali; Sangeetha V Naveen; G Krishnamurithy; Robert McKean; Tunku Kamarul (PLoS ONE, 2014)
A comparative study on the in vitro osteogenic potential of electrospun poly-L-lactide/hydroxyapatite/collagen (PLLA/HA/Col, PLLA/HA, and PLLA/Col) scaffolds was conducted. The morphology, chemical composition, and surface roughness of the fibrous scaffolds were examined. Furthermore, cell attachment, distribution, morphology, mineralization, extracellular matrix protein localization, and gene expression of human mesenchymal stromal cells (hMSCs) differentiated on the fibrous scaffolds PLLA/Col/HA, PLLA/Col, and PLLA/HA were also analyzed. The electrospun scaffolds with a diameter of 200-950 nm demonstrated well-formed interconnected fibrous network structure, which supported the growth of hMSCs. When compared with PLLA/H%A and PLLA/Col scaffolds, PLLA/Col/HA scaffolds presented a higher density of viable cells and significant upregulation of genes associated with osteogenic lineage, which were achieved without the use of specific medium or growth factors. These results were supported by the elevated levels of calcium, osteocalcin, and mineralization (P<0.05) observed at different time points (0, 7, 14, and 21 days). Furthermore, electron microscopic observations and fibronectin localization revealed that PLLA/Col/HA scaffolds exhibited superior osteoinductivity, when compared with PLLA/Col or PLLA/HA scaffolds. These findings indicated that the fibrous structure and synergistic action of Col and nano-HA with high-molecular-weight PLLA played a vital role in inducing osteogenic differentiation of hMSCs. The data obtained in this study demonstrated that the developed fibrous PLLA/Col/HA biocomposite scaffold may be supportive for stem cell based therapies for bone repair, when compared with the other two scaffolds.